Malay adolescents experiences with divorced and remarried parent(s) : a phenomenological study - Sharifah Aishah Syed Hamzah (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Parental divorce is an important topic in the family institution, especially when the divorce impacts the people around them. This study examined the inner thoughts and feelings of the adolescents in coping with parental divorce and subsequent remarriage in Malaysia among Malay adolescents. The study also investigates how the pre- and post-divorce circumstances affect these adolescents. A qualitative research design using semi-structured interviews along with written essay questions was chosen as the method of the study. Five participants were chosen: one male and four females from Peninsular Malaysia were interviewed. Based on the data analysis, four categories with 15 concepts were extracted from the semi-structured interview and written essays. The four categories are Resentful, Lost Hope, Mental Conflict, and Maturity. The categories were abstracted from the pre- and post-divorce events. More negative than positive effects were detected from this study.